China’s Strategic Influence on US Foreign Relations in the Early 21st Century (Prithvi Academic Journal, 2025)
The research investigates China’s foreign policy impact on U.S. diplomatic relations during the start of the twenty-first century from the perspective of continuous changes in superpower relationships. China developed into an international economic and political power after many years of staying isolated, before it transformed its relationship with the United States. The noticeable economic expansion between the United States and China occurred despite sanctions that followed the Tiananmen Square protests in 1989. The research examines both the cooperative phases and competitive moments to evaluate China's role in the world system under U.S. leadership. The study incorporates data from trade statistics and secondary resources, together with qualitative and quantitative analytical approaches to assess whether China’s rise opposes U.S. leadership or supports its international interests. The findings suggest that China’s long-term strategic preference supports cooperation rather than competition because it prefers to establish itself within the existing international structures. The analysis concludes that U.S.-China relations develop through complex interdependence as the two nations sustain their bilateral relationship despite their fundamental political conflicts.